Nanoparticles alleviate non-alcoholic steatohepatitis via ER stress sensor-mediated intestinal barrier damage and gut dysbiosis - Zhu, Manman; Cheng, Yong; Tang, Yue; Li, Shuojiao; Rao, Peng; Zhang, Guiyang; Xiao, Lei; Liu, Jiatao (Frontiers in Microbiology, 2024)
The gut microbiota play an important role in the development of nonalcoholic steatohepatitis (NASH), but the underlying mechanism is unclear. It has been found that XBP1s plays an important role in regulating inflammation, lipid metabolism and maintaining the integrity of intestinal barrier. However, whether XBP1s modulate the development of NASH by regulating the integrity of the intestinal barrier and altering the composition of the gut microbiota remains unknown. Mice fed with fat-, fructose-, cholesterol-rich (FFC) diet for 24 weeks successfully established NASH model, as demonstrated by significant hepatic steatosis, inflammation, hepatocyte injury and fibrosis. The profile of gut microbiota dynamically changed with the different stages of NAFLD via 16S rDNA sequencing the faeces from mice fed with FFC diet for 0, 12 or 24 weekor NASH mice treated with FT@XBP1.NASH mice had significantly higher abundance of Firmicutes, Blautia and Bacteroides, and lower abundance of Bifidobacterium and GCA-900066575. FT@XBP1 supplementation had a significantly attenuated effect on FFC diet-induced weight gain, hepatic fat accumulation, dyslipidemia, inflammatory cytokines, ER stress and fibrosis. In particular, FT@XBP1 modulates the composition of the intestinal flora, for example NASH mice demonstrated higher abundance of Blautia and Bacteroides, and lower abundance of Actinobacteriota, Muribaculaceae and Bifidobacterium, which were partially restored by FT@XBP1 treatment. Mechanistically, FT@XBP1 increased the expression of ZO-1 in the intestine and had potential to restore intestinal barrier integrity and improve antimicrobial defence to alleviate enterogenic endotoxemia and activation of inflammatory signaling pathways. Regulation of the key transcription factor XBP1s can partially restore the intestinal microbiota structure, maintain the integrity of intestinal mucosal barrier, and prevent the progression of NASH, which providing new evidence for treating NASH.